Social Pathologist and Code of Conduct (Nepalese Medical Journal, 2018)
We have integrated social media into our lives by choice and we in the medical practice, amidst our busy schedules, have been using it for easy connectivity with friends and families and also, if not importantly, for our continued education. With the advent of digital pathology the image sharing has become much easier. This has been further expedited by cameras on the smart phones and editing apps. We have several groups dedicated to numerous subspecialties in pathology and they make peer reviewing and sharing of images, articles and relevant advances relatively easy. However, like all human endeavors, the lines can be crossed. Hence balance has to be maintained regarding patient privacy and our own professional needs. American College of Physicians and the Federation of State Medical Boards has proposed guidelines for the same. These guidelines will be amended and improved in future with techniqual advances.Nepalese Medical Journal, vol.1, No. 1, 2018, Page: 39-42